2021
DOI: 10.1111/nyas.14672
|View full text |Cite
|
Sign up to set email alerts
|

Speech breathing: variable but individual over time and according to limb movements

Abstract: Breathing is variable but also highly individual. Since the 1980s, evidence of a ventilatory personality has been observed in different physiological studies. This original term refers to within-speaker consistency in breathing characteristics across days or even years. Speech breathing is a specific way to control ventilation while supporting speech planning and phonation constraints. It is highly variable between speakers but also for the same speaker, depending on utterance properties, bodily actions, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The effect of limb acceleration on speech acoustics was investigated based on the recording of speech, breathing, and limb motion data during a narrative task in different conditions of limb movements (see Ref. 8 , for more details). The data were recorded at the Leibniz-Zentrum Allgemeine Sprachwissenschaft (ZAS).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of limb acceleration on speech acoustics was investigated based on the recording of speech, breathing, and limb motion data during a narrative task in different conditions of limb movements (see Ref. 8 , for more details). The data were recorded at the Leibniz-Zentrum Allgemeine Sprachwissenschaft (ZAS).…”
Section: Methodsmentioning
confidence: 99%
“…Note that breathing was synchronously monitored using an Inductotrace inductance plethysmography system (see Ref. 8 ). However, we did not analyze breathing for the current purpose: since the time window analyzed is around 400 ms around the physical impulse, it is impossible to know whether the potential bumps we could find in breathing kinematics at the time of occurrence of the physical impulses come from a shift of the belts due to the cycling movement or from a real effect of the impulse on the thoracic cage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of it, the link between definite cognitive demands and breathing during speech remains unclear. Previous research has demonstrated that speech generation entails strong adaptations in breathing patterns related to linguistic and cognitive requirements ( Serre et al, 2021 ). For instance, important differences in respiratory outcomes have been reported in healthy individuals required to read short text passages versus executing spontaneous speech during free talking ( Winkworth et al, 1994 , 1995 ; Mitchell et al, 1996 ; Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%